Samuel Marsden the great survivor - YARWOOD, A.T. (Melbourne, Aust Melbourne University, 1977)
Includes bibliographical references and index.
Keywords: Samuel Marsden, 1764-1838.; Church of England -- biography; New South Wales -- biography